The Influence of Brand Image and Electronic Word Of Mouth on the Brand Trust of BSI Hajj Indonesia Savings Customers at Bank BSI KCP Jatinangor UNPAD - Hilmi, Salwaa Aqilah; Nur'aeni, Nur'aeni (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Based on the results of observations and interviews, this study was motivated by the fluctuating number of customers of BSI Tabungan Haji Indonesia. This fluctuation is influenced by several factors, including Brand Image and Electronic Word Of Mouth (e-WOM). In May 2023, BSI experienced a system error incident, which was suspected to be caused by a cyberattack. which affected customer perceptions and trust in BSI, due to the widespread dissemination of negative information through e-WOM. This study aims to analyze the impact of brand image and electronic word of mouth on brand trust among BSI Tabungan haji Indonesia customers at Bank Syariah Indonesia KCP Jatinangor UNPAD, both individually and simultaneously. The object of this study is the customers of BSI Tabungan Haji Indonesia at Bank Syariah Indonesia KCP Jatinangor UNPAD. This research employs a quantitative associative approach using primary data. Data collection techniques include observation, interviews, literature study, and questionnaires. The sampling technique used is purposive sampling, with a total of 97 respondents selected based on specific criteria from a population of 2,960 customers. The results show that Brand Image has a significant effect on Brand Trust among BSI Tabungan Haji Indonesia customers at BSI KCP Jatinangor UNPAD by 21.2%, with the result tcount > ttable (5.050 > 1.6612). there is also Electronic Word Of Mouth has a significant effect on Brand Trust among BSI Tabungan Haji Indonesia customers at BSI KCP Jatinangor UNPAD by 23,4% with the result tcount > ttable (5.390 > 1.6612). Simultaneously, Brand Image and Electronic Word Of Mouth significantly influence Brand Trust among BSI Tabungan Haji Indonesia customers at BSI KCP Jatinangor UNPAD by 26.8% with the result Fcount > Ftable (17.183 > 2.36).